1999
DOI: 10.1051/aas:1999489
|View full text |Cite
|
Sign up to set email alerts
|

Radial velocities

Abstract: Abstract. Radial velocities have been determined for a sample of 2930 B2-F5 stars, 95% observed by the Hipparcos satellite in the north hemisphere and 80% without reliable radial velocity up to now. Observations were obtained at the Observatoire de Haute Provence with a dispersion of 80Å mm −1 with the aim of studying stellar and galactic dynamics. Radial velocities have been measured by correlation with templates of the same spectral class. The mean obtained precision is 3.0 km s −1 with three observations. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
4
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 10 publications
12
113
4
1
Order By: Relevance
“…Target selection 32 targets from the HIPPARCOS catalogue have been selected according to the following criteria: 1) brighter than magnitude 8; 2) spectral type ranging from A0 to F2; 3) showing some indication of radial velocity variability (Grenier et al 1999); and 4) preferentially with less than ten references in the bibliography recorded in the SIMBAD database at the CDS. The selected targets are ordered by increasing HD number in Table 1, with the HIP number (Col. 2), number of references in SIMBAD (Col. 3), V magnitude (Col. 4) and spectral type (Col. 5) from Grenier et al (1999).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target selection 32 targets from the HIPPARCOS catalogue have been selected according to the following criteria: 1) brighter than magnitude 8; 2) spectral type ranging from A0 to F2; 3) showing some indication of radial velocity variability (Grenier et al 1999); and 4) preferentially with less than ten references in the bibliography recorded in the SIMBAD database at the CDS. The selected targets are ordered by increasing HD number in Table 1, with the HIP number (Col. 2), number of references in SIMBAD (Col. 3), V magnitude (Col. 4) and spectral type (Col. 5) from Grenier et al (1999).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…In their catalogue of stellar radial velocities, Grenier et al (1999) noticed that 32% of the sample of B8-F2 type stars observed by the Hipparcos satellite have variable velocities and assumed that this variability was due to multiplicity only. Though this conclusion remains valid when performing statistics on the overall occurrence of multiplicity, it is realistic to think that some of the studied stars are also non-radial pulsators showing line profile variations (LPVs).…”
Section: Introductionmentioning
confidence: 99%
“…Enfin, les vitesses radiales obtenues par Fehrenbach et sonéquipe (Fehrenbach et al 1987)à l'aide du spectrographe Marly ontété améliorées par la mesure de nouveaux clichés obtenus au même spectrographe (Grenier et al 1999). Nous avons donc introduit ces nouveaux résultatsà la place des anciens, mais nous n'avons pas pris en compte les résultats concernant leś etoiles ne figurant pas dans la première publication.…”
Section: Origine Des Vitesses Radiales Utiliséesunclassified
“…In the older literature spectral types A2 V (Osawa 1959;Eggen 1960) and A2 IV (Cowley et al 1969) can be found, whereas Abt & Morell (1995) or Grenier et al (1999) give A2 III. Therefore, in Table 4 we have calculated the eclipse parameters for two models which fulfill the mass function: one with A2 V + K7 V, the other with A2 III + K3 V. The masses, radii and semi-major axis a are expressed in corresponding solar units, and the minimum distance of both components a min = (1−e) a in radii of the primary.…”
Section: Resultsmentioning
confidence: 94%